Juridical Analysis of the Policy Guarantee Program in Increasing Policyholder Trust According to Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector - Wicaksono, Muhammad Bagas Ragil (CV. Publikasi Indonesia, 2025)
Indonesia’s insurance industry, while growing, faces significant challenges due to inadequate legal protection for policyholders, particularly when insurance companies become insolvent or fail to fulfill claim obligations. This situation undermines policyholder trust and limits the sector’s economic contribution. The recent enactment of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector introduces the Policy Guarantee Program, aiming to safeguard policyholders’ rights by ensuring compensation in cases of insurer bankruptcy or liquidation. This study employs an empirical juridical approach, combining normative legal analysis with sociological research through interviews with policyholders, to assess the implementation of this law and its impact on policyholder trust. Findings reveal that the program enhances legal certainty and consumer confidence by prioritizing policyholder claims and establishing the Deposit Insurance Corporation as the guarantor. Despite this progress, challenges remain in public awareness and program accessibility. The study recommends ongoing regulatory refinement, strengthened supervision, and expanded financial literacy efforts to maximize the program’s effectiveness. The Policy Guarantee Program aligns with Indonesia’s financial sector roadmap and promises to support sustainable insurance industry growth by restoring public trust.